THE CONTROLLER OF FUZZY LOGIC IN THE MANAGEMENT OF TECHNOLOGICAL PROCESSES - S. V. Shilkina; E. N. Fokina (Вестник СибАДИ)
Introduction. The current stage of progress is associated with the development and implementation of intelligent systems and technologies that provide the formation of clear solutions based on fuzzy rules, fuzzy conclusion and fuzzy control. However, the classical control methods work well only with a completely deterministic control object and deterministic environment, but for fuzzy information systems and highly complex control object, fuzzy control methods are optimal. Material and methods. Moreover, the process of decision-making by a person in the management of technological processes is modeled and simulated by a fuzzy controller with a base of rules. In recent years, “fuzzy” control has been successfully used to manage and operate a number of systems. Discussion and results. Therefore, this article is devoted to the consideration of fuzzy logic controller’s application in management systems and existing research methods’ analysis in the field of intelligent control technologies for solving the problems of adaptation of applied models and algorithms to various objects and systems, particularly to the systems for maintaining the microclimate parameters of the building’s life support environment, and also to the basic parameters of increasing the economic efficiency of using the fuzzy logic controller in the control system.Conclusion. Analyzed control methods based on fuzzy logic are applicable to various technological objects and systems. As a further study, it is planned to consider the issues of fuzzy control of various life support systems of a modern building.